Mathematics Communication Skills Reviewed by Emotional Quotient of Primary School Students on Circ Typed Cooperative Learning - Safitri, Safitri; Dwijanto, Dwijanto; Yusuf, Amin (Educational Management, 2020)
Improving communication skill through mathematics learning should be owned by students in their daily lives. Such effort should be done to reach mathematics learning purpose. This research aims to create review effectiveness of CIRC typed cooperative learning to students’ mathematics communication skills, and obtain the existence of mathematics communication skill differences reviewed by student emotional quotient. This mixed method research used triangulation concurrent method. The subjects were fifth graders of 03 Public Primary School Ngaliyan Semarang. The findings showed that CIRC typed cooperative learning reached classical accomplishment with only 68.57%. It meant it had not reached classical accomplishment criteria 70%. The average of mathematics communication skill test by using CIRC was 71.54, better than those taught by discovery learning with 54.43. There was improvement of the students’ mathematics communication. And the emotional quotients of the students did not influence their mathematics communication skill improvement. Thus, it could be concluded that CIRC typed cooperative learning could effectively improve mathematics communication skills of the students. Based on the findings, it is suggested to create questions emphasizing on indicators and implementing emotional quotients as efforts to improve mathematics communication skills.